Laminin-Inspired Cell-Instructive Microenvironments for Neural Stem Cells - Barros, D (2019)
Laminin is a heterotrimeric glycoprotein with a key role in the formation and maintenance of the basement membrane architecture and properties, as well as on the modulation of several biological functions, including cell adhesion, migration, differentiation and matrix-mediated signaling. In the central nervous system (CNS), laminin is differentially expressed during development and homeostasis, with an impact on the modulation of cell function and fate. Within neurogenic niches, laminin is one of the most important and well described extracellular matrix (ECM) proteins. Specifically, efforts have been made to understand laminin assembly, domain architecture, and interaction of its different bioactive domains with cell surface receptors, soluble signaling molecules, and ECM proteins, to gain insight into the role of this ECM protein and its receptors on the modulation of neurogenesis, both in homeostasis and during repair. This is also expected to provide a rational basis for the design of biomaterial-based matrices mirroring the biological properties of the basement membrane of neural stem cell niches, for application in neural tissue repair and cell transplantation. This review provides a general overview of laminin structure and domain architecture, as well as the main biological functions mediated by this heterotrimeric glycoprotein. The expression and distribution of laminin in the CNS and, more specifically, its role within adult neural stem cell niches is summarized. Additionally, a detailed overview on the use of full-length laminin and laminin derived peptide/recombinant laminin fragments for the development of hydrogels for mimicking the neurogenic niche microenvironment is given. Finally, the main challenges associated with the development of laminin-inspired hydrogels and the hurdles to overcome for these to progress from bench to bedside are discussed.